2020
DOI: 10.3390/catal10060672
|View full text |Cite
|
Sign up to set email alerts
|

Defective TiO2 Core-Shell Magnetic Photocatalyst Modified with Plasmonic Nanoparticles for Visible Light-Induced Photocatalytic Activity

Abstract: In the presented work, for the first time, the metal-modified defective titanium(IV) oxide nanoparticles with well-defined titanium vacancies, was successfully obtained. Introducing platinum and copper nanoparticles (NPs) as surface modifiers of defective d-TiO2 significantly increased the photocatalytic activity in both UV-Vis and Vis light ranges. Moreover, metal NPs deposition on the magnetic core allowed for the effective separation and reuse of the nanometer-sized photocatalyst from the suspension after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Core-shell NPs are also considered as another 0D morphology with interesting properties due to the formation of a functional system from the integration of individual components, improving chemical and physical properties, such as dispersibility, functionality, and stability, that might not be obtained for sole components [79,80]. The core-shell titania-structured materials are considered as highly wanted, not only due to enhanced stability and activity, but also because of improved recycling ability when a magnetic component is used in the composite [81,82]. Indeed, Bielan et al have found that the modification of magnetic core-shell particles (Fe 3 O 4 @SiO 2 /TiO 2 ) with NPs of platinum and/or copper has resulted in a high enhancement of hydrogen evolution (methanol as a hole scavenger) even by two orders of magnitude under UV/vis irradiation [83].…”
Section: Zero-dimension (0d) Photocatalystsmentioning
confidence: 99%
“…Core-shell NPs are also considered as another 0D morphology with interesting properties due to the formation of a functional system from the integration of individual components, improving chemical and physical properties, such as dispersibility, functionality, and stability, that might not be obtained for sole components [79,80]. The core-shell titania-structured materials are considered as highly wanted, not only due to enhanced stability and activity, but also because of improved recycling ability when a magnetic component is used in the composite [81,82]. Indeed, Bielan et al have found that the modification of magnetic core-shell particles (Fe 3 O 4 @SiO 2 /TiO 2 ) with NPs of platinum and/or copper has resulted in a high enhancement of hydrogen evolution (methanol as a hole scavenger) even by two orders of magnitude under UV/vis irradiation [83].…”
Section: Zero-dimension (0d) Photocatalystsmentioning
confidence: 99%
“…The concept of optimal titania layer has been suggested as inconsistent with an electron transfer mechanism since an increase in titania width might result in activity decrease (high probability of electrons' trapping before their arrival at the photocatalyst surface). Interesting approach has been proposed by Bielan et al for plasmonic photocatalysts (TiO2 with Pt and Cu/CuxO) supported on magnetic core for easy separation of photocatalyst after reaction ( Figure 13) [103,104]. The photocatalysts exhibit good reusability with almost same reaction rate for fresh and reused (after recovery by a magnet) photocatalysts during consequent photocatalytic cycles.…”
Section: Other Particulate Plasmonic Photocatalysts With Advanced Mormentioning
confidence: 99%
“…Although, Pt-modified titania samples show vis activity due to LSPR, the magnetic photocatalysts lose the vis response, probably because of "hot" electron trapping by magnetic core (Pt→TiO 2 →Fe 3 O 4 /SiO 2 ) [103], similarly as suggested for bimetallic [97] and hybrid (co-modified with ruthenium dye [105][106][107]) plasmonic photocatalysts. Interestingly, self-doped titania (titania with defects) significantly improves the photocatalytic activity under vis irradiation for both supported (on magnetic core) and unsupported plasmonic photocatalysts [104]. Interesting approach has been proposed by Bielan et al for plasmonic photocatalysts (TiO2 with Pt and Cu/CuxO) supported on magnetic core for easy separation of photocatalyst after reaction ( Figure 13) [103,104].…”
Section: One-dimensional Plasmonic Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations